The Short-Term Value of the “Healthy Primary School of the Future” Initiative: A Social Return on Investment Analysis - Marije Oosterhoff; Onno C. P. van Schayck; Nina H. M. Bartelink; Hans Bosma; Maartje Willeboordse; Bjorn Winkens; Manuela A. Joore (Frontiers in Public Health, 2020)
Background: This study examines the social return on investment (SROI) of the “Healthy Primary School of the Future” initiative after 2 years.Methods: Healthy Primary Schools of the Future (HPSF) provide a healthy lunch and daily structured physical activity sessions, whereas Physical Activity Schools (PAS) focus on physical activity only. We evaluated the 2-years investments and effects (N = 1,676 children) of both school environments (four schools) compared to control schools (four schools). Investments and outcomes were grouped within the healthcare, education, household & leisure, and labor & social security sector. Outcomes that could be expressed in monetary terms were used for the calculation of social return on investment.Results: HPSF and PAS created outcomes for the healthcare sector by favorable changes in health behaviors, body mass index [both significant], and medical resource use [not significant]. Outcomes for the education sector included a favorable impact on perceived social behaviors and school satisfaction, and absenteeism from school [latter not significant], and more engagement with the community was experienced. The per child investments, €859 (HPSF) and €1017 (PAS), generated a benefit of €8 (HPSF) and €49 (PAS) due to reduced school absenteeism and medical resource use.Conclusions: Within 2 years of intervention implementation, the HPSF initiative created outcomes in several sectors, but the benefits did not outweigh the investments. Follow-up assessments as well as modeling long-term outcomes are needed to assess the total value of the interventions. Until then, the SROI framework can inform strategies for obtaining stakeholder support and intervention implementation.Trial registration: The study was registered in the ClinicalTrials.gov database on 14 June 2016 (NCT02800616).